Healthcare associated infections by multidrug resistant in pediatric intensive care: Analysis of four years. - Araujo da Silva, André Ricardo; Teixeira, Cristiane Henriques; Werneck, Lúcia Santos (International Journal of Infection Control, 2014)
Objective: To report healthcare associated infections (HAI) in intensive care units of children, caused by multidrug resistant bacteria, and measures to control them. Methods: a retrospective descriptive study of all HAI in three pediatric intensive care units and one neonatal intensive care unit of Prontobaby Hospital da Criança, Rio de Janeiro, Brazil. Results: Between 2009 and 2012 we had 36,883 patients-days which 10,442 were from NICU and 26,441 from the PICUs. We reported 482 healthcare-related infections (109 from NICU and 373 from PICU). Gram negative bacteria were the most prevalent group, also in NICU (22.9%) as in PICU (35.9%). The rates of multiresistant Gram positive bacteria (MRSA and CoNS multiresistant) of HAI in the PICUs and NICU were 22% (22/100) and 13,6% (3/22) respectively. The rates of multiresistant Gram negative bacteria (ESBL group, P.aeruginosa resistant to carbapenem, Acinetobacter sp multiresistant, B.cepaciae and S. maltophilia) in PICUs and NICU were 49,3% (66/134) and 56% (14/25) respectively. Ventilator-associated pneumonia was the most common type of infection (incidence density rate of 7,0 per 1000 VM-days) in PICU. A bundle of measures (training of team assistance, oral chlorexidine to all intubated children and use of bacteriological filters in expiration phase) was implemented in the two last years of study and reduced the number of VAP to 2,2 per 1000 VM-days. Conclusion: We found higher rates of multiresistant Gram negative bacteria also in PICU as NICU and a bundle of measures to control VAP in PICU was a well done intervention.